PS15cey and PS17cke: prospective candidates from the Pan-STARRS Search for kilonovae. Issue 3 (13th November 2020) - McBrien, O R; Smartt, S J; Huber, M E; Rest, A; Chambers, K C; Barbieri, C; Bulla, M; Jha, S; Gromadzki, M; Srivastav, S; Smith, K W; Young, D R; et al.
ABSTRACT: Time domain astronomy was revolutionized with the discovery of the first kilonova, AT2017gfo, in August 2017, which was associated with the gravitational wave signal GW170817. Since this event, numerous wide-field surveys have been optimizing search strategies to maximize their efficiency of detecting these fast and faint transients. With the Panoramic Survey Telescope and Rapid Response System (Pan-STARRS), we have been conducting a volume-limited survey for intrinsically faint and fast-fading events to a distance of D ≃ 200 Mpc. Two promising candidates have been identified from this archival search, with sparse data – PS15cey and PS17cke. Here, we present more detailed analysis and discussion of their nature. We observe that PS15cey was a luminous, fast-declining transient at 320 Mpc. Models of BH–NS mergers with a very stiff equation of state could possibly reproduce the luminosity and decline but the physical parameters are extreme. A more likely scenario is that this was an AT2018kzr-like merger event. PS17cke was a faint and fast-declining event at 15 Mpc. We explore several explosion scenarios of this transient including models of it as a NS–NS and BH–NS merger, the outburst of a massive luminous star, and compare it against other known fast-fading transients. Although there is uncertainty in the explosion scenario due to difficulty in measuring the explosion epoch, we find PS17cke to be a plausible kilonova candidate from the model comparisons.